Penguatan Fungsi Pengawasan DPR Melalui Perubahan Undang-Undang Nomor 10 Tahun 1954 Tentang Hak Angket - Fitria Fitria (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2014)
Abstract: Strenghtening DPR’s Oversight Rights Through Out the Revision of Act No. 10 Year 1954 on Oversight Rights. Oversight right owned by the DPR is aimed to bring its function to be more effective. However, the implementation of this right is still on question since the result of the oversight rights is placed in the